First-Line (1L) Treatment Decision Patterns and Survival of Hormone Receptor (HR)-Positive/HER2-Negative Advanced Breast Cancer (ABC) Patients in a Latin American (LATAM) Public Institution - Guillermo Valencia; Patricia Rioja; Miguel Chirito; Olenka Peralta; Jorge Sánchez; Connie Rabanal; Raúl Mantilla; Zaida Morante; Hugo Fuentes; Carlos Castaneda; Tatiana Vidaurre; Cristian Pacheco; et al. (Current Oncology)
Advanced breast cancer is an incurable disease, with a median overall survival of 3 years, including in countries without access problems. Although chemotherapy is reserved in some cases, it is still used in many countries as a first-line therapy. The aim of our study is to evaluate the first-line treatment choices and the factors that influence therapeutic decisions. A retrospective analysis was conducted of hormone receptor (+)/HER2 (−) advanced breast cancer patients classified into three groups according to the first-line and second-line treatment received: endocrine therapy–chemotherapy, endocrine therapy–endocrine therapy and chemotherapy–endocrine therapy. Additionally, we explored the overall survival of sequencing therapy groups. First-line chemotherapy was chosen in 34% of patients. Also, around 60% of our patients met the “aggressive disease” criteria from the RIGHT Choice trial, justifying the use of chemotherapy in a population with poor prognosis. Furthermore, de novo and progressive disease were prognostic factors that influenced the use of chemotherapy as a first-line treatment. Regarding overall survival, the sequencing treatment groups in this trial saw an increase in survival compared with patients of the MONALEESA trials (endocrine therapy alone arms). No significant differences in progression-free survival or overall survival were found in the treatment sequencing groups. There was a higher use of chemotherapy as a first-line therapy, with de novo and “aggressive disease” criteria being the main factors to influence the decision.